Desenvolvimento, construção e avaliação de um protótipo de fatiadora de cactácea forrageira - Fernandes, Francisco Ronaldo Belem (2018)
Family farming in Brazil is extremely heterogeneous, since it includes very poor families and families with large resources. However, modernization in agriculture has promoted a profound restructuring of productive spaces in the countryside. Forage production is a complex system that requires the simultaneous use of several machines, among which the harvesters. The objective of this work is to develop, construct and evaluate in field conditions a prototype of a forage cactus slicer for family farming. The work was developed in three stages: the first: Elaboration of the conceptual project, conducted in the Laboratory of accident investigation with agricultural machines, belonging to the Federal University of Ceará. The second: the construction of the prototype was carried out at the Geras Auto Parts workshop in Tauá-Ce. Third: Evaluation was conducted in the experimental area of the Federal Institute of Education, Science and Technology of Ceará IFCE Campus Tauá. The conceptual development of an equipment to perform the harvest of forage plants, consisted in the combination of several systems. Due to the morphological characteristics of some forage species such as forage palm and mandacaru, it was decided to develop only the processing mechanism for forage cactus, called native and cultivated forage cactus slicer, can be activated by at least two sources of power, electric motor and coupled to the agricultural tractor through the power take-off. The equipment will be subjected to real working conditions, so that the operational performance of the equipment can be determined. For this purpose, forage palm and mandacaru will be used as plant material. After defining the mean standard error and considering a β error of 10%, through the graph of operating characteristic curves the minimum number of samples was determined equal to 15 samples, however, for the evaluation of the machine we chose to collect 20 samples to increase the possibilities of normality of the data. The experimental design was completely randomized with 2x2 factorial scheme, being two power sources and two genera of cactus, Cereus and Opuntia. The variables evaluated in the field test were production capacity (CP), total process losses (PTP), particle size (TP), uniform sized particles, reprocessing particles and splintered particles. After the data collection, a descriptive statistical analysis will be performed. The normality of the data will be attested by the coefficients of symmetry and kurtosis. If they present a normal distribution will be done analysis of variance using the tukey test at 5% probability. Analyzing the PTP and CP data obtained during the slicing process the cactacea slicer presented for the forage palm mean values of 0, 078 and 1646.5 kg for the rotation of 602 rpm. On the other hand, for the particle and particle variables, the mean values obtained in this order for the rotation were 23.6 and 76.4%. When measuring the particle size after the process, it was observed that the sliced material presented an average value of 2.95 cm.